Pengaruh Ukuran Perusahaan, Likuiditas, Leverage, dan Margin Laba Kotor terhadap Pemilihan Metode Penilaian Persediaan - Winda Meilia; Dien Noviany Rahmatika (Permana : Jurnal Perpajakan, Manajemen, dan Akuntansi, 2020)
This study aimssto detrmine the Effectt of Company Size, Liquidty, Leverage And Profit Margin Against Selection Inventory Valuation Method (Case Study in the food and baverage company listd on the Indonesia Stock Exchage year 2016-2018). The population of thissstudy is a fooddand beverage compny listed on the Indonesia StockkExchange in the 2015-2018 period. The research sample consisted of 36 companies. The sampling technique with purposive sampling technique. The datas used isssecondary data on annual reports offfood ands beverage companies listd on the Indonesiia Stock Exchange. This research uses logistic analysis method with SPSS program. The results showed that company size effectson the selction of inventorys valuation methods with a significant value of 0,023. Liquidity does not affect theeselction of inventory valuations methods with a significant value of 0,449. Leverage does not affect theeselection oof inventoryyvaluation methods with a significant value of 0,926. And the gross profit margin effects on the selction ofiinventory valuation methods with a significant value of 0,027.